Investment taxation : practical tax strategies for financial instruments - Hibschweiler, Arlene M.; Kopin, Marion (New York : McGraw-Hill, 2003)
Helps you understand the tax treatment of stocks, bonds, options, and other popular investments. This book is useful for financial planners, attorneys, accountants, brokers, traders, bankers, entrepreneurs, investors, potential investors, and students.
Includes index.
oif 08/08/16
Loan
Keywords: Investments; Financial instruments; Taxation; Law and legislaation; United States